Towards sustainable education: exploring the intention to pursue vocational higher education among senior high school students in Ningxia, China / Tian Jing ... [et al.] - Jing, Tian; Chung, Ellen; Gregory, Margaret Lucy; Abdullah, Johari (Universiti Teknologi MARA, 2024)
As part of the national agenda to inculcate more skilled and technical talents to boost the economy, China has created the most extensive vocational education in the world. Yet enrolment for vocational higher education is still relatively low, and this can derail its national agenda. This study aims to explore the intention to pursue vocational higher education among general senior high school students in Ningxia using the Theory of Planned Behaviour. Data was collected from 432 senior high school students in Ningxia, China, using a survey instrument which contains four variables with 28 items. These independent variables are attitude towards pursuing vocational higher education, subjective norms, perceived behavioural control; while intention to pursue vocational higher education is the dependent variable. All four variables have moderate to strong positive correlations with each other. Multiple regression analysis showed that attitude and subjective norms predict the intention to pursue vocational higher education among the senior three general senior high school students. However, perceived behavioural control does not have this predictive power. This study is significant as it sheds more light into what factors contribute to the intention to pursue a vocational higher education in Ningxia using the Theory of Planned Behaviour,. Finally, based on the findings of this study, recommendation were put forward for policy makers to increase enrolment for higher vocational education to meet the country’s demand for skilled workers.